Dry deposition velocities of particles on grass: Field experimental data and comparison with models. (December 2018) - Connan, O.; Pellerin, G.; Maro, D.; Damay, P.; Hébert, D.; Roupsard, P.; Rozet, M.; Laguionie, P.
Abstract: Aerosols emitted into the atmosphere are dispersed by atmospheric air masses and then removed by dry or wet deposition processes. In some cases, if there are no episodes of precipitation, dry deposition may be the main processes in particular on a local scale. Dry deposition is characterized by the dry deposition velocity Vd (m.s −1 ), which is generally standardized at the friction velocity u* (m.s −1 ). From 2005–2016, we conducted experimental campaigns on-site with fluorescein tracer to determine dry deposition velocity of aerosols on grass. The particle sizes tested were 0.24, 0.27, 0.5, 0.6, 1.2, 3, and 7.8 µm. We described here the experimental method, the results obtained in terms of Vd/u* by particle size and we compared our results to the values usually simulated from the main models used by the scientific community. The results show that the Vd/u* parameter varies in a range from 2 to 6 10 −3 for particle diameters from 0.2 to 1.2 µm. Beyond 1.2 µm the Vd/u* ratio increases rapidly with a value of 5.4 10 −2 to 7.8 µm. Based on our experimental results, Vd/u* relationships were proposed for potential applications in operational models for a grass-type rural cover, which has a constant mean value of 3.7 ± 1.9 10 −3 for particles in the size range of 0.2 and 1.2 µm, and as a linear function of particle size (Dp, diameter) expressed as 0.0082 × [Dp]− 0.0106 for larger particles between 1.2 and 8 µm. Highlights: Dry deposition velocities of fluorescein aerosol particles between 0.24 and 7.8 µm. On-site measurements of dry deposition velocities on grass. Correlation between the dry deposition velocities and the diameter of the particles. Vd/u* varies in a range 2 10 −3 to 6 10 −3, for particles diameters from 0.2 to 1.2 µm. Beyond 1 µm, Vd/u* increase rapidly, with value of 5.1 10 −2 to 7.8 µm.